STRUKTUR KEPEMILIKAN SAHAM TERHADAP KEBIJAKAN UTANG PERUSAHAAN DI BURSA EFEK INDONESIA - Luh Gede Sri Artini; Ni Nyoman Ayu Diantini (University of Merdeka Malang, 2014)
This paper examined the effects of insider ownership, institutional investors and shareholders dispersion ondebt ratio by pooled regression model. The research Population was all the firms in LQ 45 in Indonesia StockExchange (IDX) from 2009 until 2012, and sampling conducted in this research was purposive samplingmethod. Based on the criteria obtained by purposive sampling, 15 companies were eligible to be utilized as theresearch sample. The results of this research were that the impact of insider ownership was positive significanton debt ratio, the institutional investor had a significant positive impact on debt ratio, shareholder dispersionwas not significantly effect on debt ratio.